The Relationship Between Body Mass Index and Different Regional Patterns of Lymph Node Involvement in Papillary Thyroid Cancers - Li, Changlin; Dionigi, Gianlorenzo; Liang, Nan; Guan, Haixia; Sun, Hui (Frontiers in Oncology, 2021)
Introduction Lymph node (LN) metastasis is the first site of metastasis of papillary thyroid cancer (PTC). LN status influences clinical management and the prognosis of patients. We explored the relationship between patient obesity and regional patterns of LN involvement in PTC. Materials and methods This study retrospectively analyzed the data from 12,772 PTC patients. The rate of LN metastasis, number of LN metastasis, maximum diameter of positive LN, number of LN dissections, and LN ratios (LNR) were compared between normal-weight and obese patients. Statistical methods have been adjusted for the confounders in hypothesis testing. Results Overweight and obesity were independent risk factor for metastatic LNs (OR1=1.125, 95% CI 1.042-1.214, P1=0.003; OR2=1.554, 95% CI 1.339-1.802, P2<0.001). Obesity was an independent risk factor for the number of metastatic CLNs (OR=1.159, 95% CI 0.975-1.377, P=0.045), however not for number of metastatic lateral LNs (P=0.907). Furthermore, obesity was not an independent risk factor for number of CLNs when dissected more than five (P=0.653), still an independent risk factors for number of metastatic lateral LNs when more than six (OR=1.185, 95% CI 1.010-1.391, P=0.037). As for LNR, obesity was an independent risk factor for the central LNR when more than 0.12 (OR1=1.099, 95% CI 1.011-1.194, P1=0.027; OR2=1.177, 95% CI 1.003-1.381, P2=0.045), for the lateral LNR more than 0.05 (P2=0.283). Conclusions Obesity was associated with poor prognoses with PTC respecting LNs. Inverse regional difference profile (central vs. lateral LNs) between obesity and number of LN dissections and LNR was discovered, suggesting caution when performing central neck dissection in obese patients.